Irrigation Fluid Temperature Modulates Coagulation and Endothelial Biomarkers in Patients Undergoing TURP: Temperature Effects on Coagulation and Endothelial Function in TURP - Gu, Min; Xu, Yanqiu (Journal of Medical Biochemistry, 2025)
Background: Irrigation fluid temperature is a critical but often overlooked factor influencing perioperative hemostasis in transurethral resection of the prostate (TURP). While the clinical consequences of hypothermia are known, its biochemical impact on coagulation and endothelial markers remains incompletely understood. Methods: Ninety patients with benign prostatic hyperplasia undergoing TURP were randomized into three groups based on irrigation fluid temperature: hypothermia (24–26 °C), mild hypothermia (28–35 °C), and preheating (36–37 °C). Peripheral blood was collected preoperatively and 6 h postoperatively to evaluate coagulation and endothelial indices, including prothrombin time (PT), activated partial thromboplastin time (APTT), platelet count (PLT), platelet aggregation rate (Pagt), and endothelin-1 (ET-1). Results: Hypothermia significantly prolonged APTT and reduced PLT and Pagt compared with preheating (all P < 0.05), indicating impaired intrinsic pathway activity and platelet dysfunction. PT remained unchanged across groups. ET-1 levels decreased in both hypothermia and preheating groups, with the greatest reduction in preheating, suggesting differential endothelial responses. Patients in the preheating group exhibited preserved coagulation stability and fewer adverse events (6.7%) compared with hypothermia (33.3%) and mild hypothermia (23.3%) groups (P = 0.038). Conclusion: Hypothermic irrigation during TURP disrupts coagulation and endothelial homeostasis, primarily via intrinsic pathway inhibition and platelet impairment. Laboratory parameters such as APTT, PLT, Pagt, and ET-1 may serve as useful indicators of hypothermia-induced coagulopathy and predictors of perioperative bleeding risk. Integration of these biomarkers into perioperative monitoring could guide thermal management strategies and improve patient outcomes.